EXPLORING THE LINK BETWEEN PHONEMIC AWARENESS AND LISTENING PERFORMANCE AMONG ENGLISH MAJORS IN PALEMBANG - Hariswan Putera Jaya; Hikmah Zalifah Putri (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
This study examined the relationship between phonemic awareness and listening performance among English major students, employing a quantitative correlational design to collect data from 83 students through a phonemic awareness assessment and a cloze listening test. The results showed that while most students demonstrated moderate levels of phonemic awareness, their listening proficiency remained low, with the majority scoring in the poor or failed categories. The analysis revealed a strong positive correlation (r = 0.772, p < 0.05) between phonemic awareness and listening performance, with phonemic awareness accounting for nearly 60% of the variance in listening achievement. These findings highlighted the foundational role of phonemic awareness in listening comprehension. The findings also suggested that explicit phonological training, authentic listening exposure, and differentiated instruction were critical to improving students' auditory processing skills. Recognizing individual learner differences and integrating systematic phonemic awareness activities into English language instruction were essential strategies for fostering comprehensive language proficiency. However, the study was limited by its sample size and geographic scope, as it focused solely on English major students from a single region. Future research involving more diverse populations across multiple institutions is recommended to enhance the generalizability of the findings.